PUBLIC INTEREST LITIGATION IN THE INTER-AMERICAN COURT OF HUMAN RIGHTS: THE PROTECTION OF INDIGENOUS PEOPLES AND THE GAP BETWEEN LEGAL VICTORIES AND SOCIAL CHANGE - Herencia Carrasco, Salvador (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2015)
The Inter-American Court of Human Rights has had a fundamental role in the protection of human rights in Latin America. Its judicial decisions have had a significant impact in national legislation, public policies and national courts. In the case of indigenous peoples, its main contributions have been related to the right to prior consultation and the protection of their territory. The purpose of this essay is to analyze the Sarayaku Case and its impact on public interest litigation. If one of the goals of strategic litigation is to foster social change, this cannot be restricted to the legal findings but must also include the active participation of victims, assuring their right of access to justice.